2005
DOI: 10.4141/p04-076
|View full text |Cite
|
Sign up to set email alerts
|

Effects of wounding and inoculation with Sclerotinia sclerotiorum on isoflavone concentrations in soybean

Abstract: . 2005. Effects of wounding and inoculation with Sclerotinia sclerotiorum on isoflavone concentrations in soybean. Can. J. Plant Sci. 85: 749-760. Isoflavones play an important role in the defense response of soybean to pathogen attack. They are involved in nodulation of legumes and are associated with human health benefits including the prevention of heart disease and cancers. Concentrations of the isoflavones daidzein, genistein, and glycitein, the glucoside conjugates daidzin, genistin and glycitin, the ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 58 publications
1
19
0
Order By: Relevance
“…These changes can also result in systemic resistance and affect performance and preference of secondary plant attackers (Stout et al 2006). Soybean responds to various stresses by biotic and abiotic factors such as wounding (Wegulo et al 2005), fungi (McDonald and Cahill 1999, Cheong et al 2000, Wegulo et al 2005, Zhang et al 2008, bacteria (Cheong et al 2000), viruses (Kelley et al 2006), nematodes (Ithal et al 2007a,b, Mazarei et al 2007), and aphids (Diaz-Montano 2006. At a cellular level, soybean responds to root infection by soybean cyst nematode with various changes in production of secondary metabolites, such as ßavonoids (Ithal et al 2007b, Jones et al 2007, and in structure of roots (Kim et al 1987).…”
Section: Discussionmentioning
confidence: 98%
“…These changes can also result in systemic resistance and affect performance and preference of secondary plant attackers (Stout et al 2006). Soybean responds to various stresses by biotic and abiotic factors such as wounding (Wegulo et al 2005), fungi (McDonald and Cahill 1999, Cheong et al 2000, Wegulo et al 2005, Zhang et al 2008, bacteria (Cheong et al 2000), viruses (Kelley et al 2006), nematodes (Ithal et al 2007a,b, Mazarei et al 2007), and aphids (Diaz-Montano 2006. At a cellular level, soybean responds to root infection by soybean cyst nematode with various changes in production of secondary metabolites, such as ßavonoids (Ithal et al 2007b, Jones et al 2007, and in structure of roots (Kim et al 1987).…”
Section: Discussionmentioning
confidence: 98%
“…The up-regulation of isoflavone biosynthesis, based on cDNA microarray data, has also been reported for soybean leaves infected with the bacterial pathogen Pseudomonas syringae (Zou et al 2005; Zabala et al 2006), the fungal pathogen Phakospora pachyrhizi (Alvord et al 2007) and the aphid Aphis glycines (Li et al 2008). An increased accumulation of isoflavones was observed in soybean leaves after various experimental treatments, including wounding (Wegulo et al 2005), inoculation with fungi (Morris et al 1991; Wegulo et al 2005), infection with phytopathogenic bacteria or nematodes (Ingham et al 1981; Osman and Fett 1983; Fett 1984; Ithal et al 2007), treatment with abiotic and biotic elicitors (Davis et al 1986), and application of herbicides (Cosio et al 1985). Considering these responses of soybean to experimental stress conditions, our observation of the sink removal-associated shift toward isoflavone accumulation, at the expense of flavones and flavonols, appears to be consistent with the activation of stress responses in soybean leaves.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al (2005) reported greater isoflavone concentrations in seeds of soybean grown at higher CO 2 levels (i.e., 650 vs. 360 µmol mol -1 of CO 2 ). Finally, stresses such as wounding or pests may also increase soybean isoflavone concentrations (Lozovaya et al 2005;Wegulo et al 2005).…”
mentioning
confidence: 99%